Rancang Bangun Sistem Informasi Penjualan “Pasar Kita” Di Pasar Tradisional Dringu Berbasis Web - Yahya Yulianto; Dyah Ariyanti; Ary Analisa Rahma (Energy - Jurnal Ilmiah Ilmu-Ilmu Teknik, 2023)
As technology advances and people's needs for shopping, considering that currently shopping can be accessed through applications. The Probolinggo District Office of Industry and Trade facilitates buying and selling without entering the market, shopping online through the WhattsApp and Instagram applications with the "Mak Blonjo" icon, the Dringu traditional market is the program's main pilot project, the lack of information about products is an obstacle in marketing. The aim of this research is to produce an application in the form of a website with the "Our Market" icon which is used as a sales information system in the Dringu traditional market so that it can make it easier for various parties to carry out fast and precise interactions and transactions. The software development method uses the waterfall method. The system created uses the PHP programming language with the CodeIgniter framework and MYSQL database. System testing is carried out using the black box testing method. While testing the satisfaction of the application uses the UAT (user acceptance test) test in the form of a questionnaire and performs a Likert scale calculation. It can be concluded that the level of satisfaction with users of the web-based "Pasar Kita" sales application reached 84.1% with 15 consumer respondents, 73.1% with 3 admin/market clerk respondents and 76.1% with 15 merchant respondents. The final result of this research is that the website-based “Pasar Kita” sales information system design can be implemented in Dringu traditional markets as a form of ordering process service.